Duodenal perforation post endoscopic retrograde cholangiopancreatography.: Miniinvasive management, a case report - Almada, Mario; Martínez, José; Muniz, Nicolás; Bonilla, Fernando; Misa, Ricardo (Cirugía del Uruguay, 2019)
Duodenal perforation secondary to endoscopic retrograde cholangiopancreatography (ERCP) is an infrequent complication that occurs in 0.01% - 2.1 % of cases. The therapeutic management, whether conservative or surgical, depends on several factors. We present the case of a woman who suffered a postERCP duodenal perforation that was treated in a mininvasive manner with a laparoscopic approach and transparietal drainage under image, avoiding traditional laparotomic surgical treatment.